Acute gastric prolapse through gastrostomy site: A surgical emergency - Reeder Wells; Christian Saliba; Vatche Melkonian; Shin Miyata; Christopher Blewett; Jose Greenspon (Elsevier, 2022)
Gastric prolapse through a gastrostomy site is a rare but potentially fatal complication in gastrostomy-tube (G-tube) dependent pediatric patients. We describe a case of strangulated gastric prolapse through a gastrostomy site in a 5-month-old patient with chronic respiratory failure, poor nutritional status, and multiple preceding G-tube complications. The patient required immediate surgical evaluation and underwent operative reduction and gastrostomy access revision within hours of presentation. There are documented cases of gastric prolapse in pediatric and adult patients, but there is no standardized management strategy. In this paper, we aim to increase vigilance of gastric prolapse in high-risk pediatric patients and to demonstrate a management plan that focuses on rapid surgical assessment and intervention to prevent significant morbidity and mortality.